Advances in space science. - Ordway, Frederick I., III (Frederick Ira), 1927-2014 (Academic Press, 1959)
Advances in Space Science, Volume 1 brings together research and developments in the astronautical sciences. This volume is composed of six chapters that also cover the field of bioastronautics, which involves the human aspects of space travel. The opening chapter deals with the orbits and interplanetary trajectories and a critical evaluation of interplanetary communications. The next chapters consider the problem of supplying power on board orbital and space vehicles, power being needed for many tasks in space, including the operation of communication systems. The remaining three chapters tre.